Demonstrating nonlinear oscillations of charged particle by the homotopy perturbation method - Al-Garalleh, B.F.; Akour, A.N.; Jaradat, E.K.; Jaradat, O.K. (Karagandy University of the name of academician E.A. Buketov, 2025)
This document describes explicitly the nonlinear equation handling the oscillation of charged particles affected by electrical field using the Homotopy Perturbation Method. This method success to construct a significant approximate solution. Our analysis has resulted in the development of an initial set of four equations that govern the oscillatory of charged particles. Following this, we have visually depicted these equations and satisfied a deep clear interpretations vision of the investigated outcomes. Our analysis has resulted in the development of an initial set of four equations that govern the oscillatory of charged particles. Following this, we have visually depicted these equations and satisfied a deep clear interpretations vision of the investigated outcomes
Keywords: Charged particle oscillation; Nonlinear harmonic equation; Homotopy Perturbation Method